On the need to follow rigorously the Rules of the Code for the subsequent designation of a nucleospecies (type species) for a nominal genus which lacked one: the case of the nominal genus Trimeresurus Lacépède, 1804 (Reptilia: Squamata: Viperidae) - David, Patrick; Vogel, Gernot; Dubois, Alain (Zootaxa, 2011)
This paper analyzes the consequences of the non-respect of the Rules of the Code to ascertain the valid subsequent designation of the nucleospecies (type species) of the nominal genus Trimeresurus Lacépède, 1804. The long accepted designation was invalid because it was based on a nominal species which was not among the prenucleospecies (originally included species) of the nominal genus. In contrast with the commonly accepted viewpoint which makes the Indian taxon Coluber gramineus Shaw, 1802 the nucleospecies of the genus, we show that this role is played by Trimeresurus viridis Lacépède, 1804, a species inhabiting the Lesser Sunda Islands and Timor and, as a nomen oblitum, a senior synonym of Trimeresurus albolabris insularis Kramer, 1977, a taxon now considered a distinct species. The important nomenclatural implications of this finding are discussed here, especially with regard to the recent splitting of the genus Trimeresurus. The generic nomen Trimeresurus should be associated with the Trimeresurus albolabris group of species currently placed in the genus or subgenus Cryptelytrops Cope, 1860. A lectophoront (lectotype) is selected and described for Trimeresurus viridis Lacépède, 1804. Coluber viridis Bechstein, 1802 is an invalid objective junior synonym of Coluber gramineus Shaw, 1802. The current content of the genus Trimeresurus and of its eight subgenera is provided. Some clarifications or improvements to the Code are suggested.